Clinical and Morphological Characteristics of Kidney Damage Caused by Covid 19 - Nurmuminovna, Gapparova Guli (American Journal of Biomedicine and Pharmacy, 2024)
SARS-CoV-2 is a betacoronavirus (b-CoV) first described in patients with pneumonia symptoms in Wuhan, China in December 2019 [2]. The emergence of a novel zoonotic betacoronavirus has been hypothesized to cause a pandemic. Based on studies of SARS-CoV and MERS-CoV, in 2015, circulating b-CoVs in bats were shown to have the potential to infect humans by using human angiotensin-converting enzyme 2 (ACE2) as a transfer protein and then binding the resulting complex to the ACE2 receptor on the host cell membrane. A similar mechanism was demonstrated by the 2002 SARS-CoV strain, and the affinity for ACE2 was enhanced in the 2003 SARS-CoV strain [13].